Routes of drug delivery - Stegemann, Sven (Henry Stewart Talks, 2022)
Routes of administration considerations, Oral administration, Parenteral administration, Cutaneous administration, Pulmonary administration, Mucosal administration, Advanced therapies, Drug delivery, Devices to support routes of administration